Cultural Adaptation, Reliability, and Validity of Neck Disability Index in Indian Rural Population. Issue 2 (15th January 2015) - Joseph, Sibi Daniel; Bellare, Bharati; Vernon, Howard
<x xml:space="preserve">Abstract</x> Study Design. A cross-sectional study to develop a cultural adaptation of the Marathi–neck disability index (NDI) and to investigate its validity and reliability. Objective. To conduct a study concerning the cultural adaptation of the NDI and investigate the validity and reliability of its Marathi version in patients with neck pain. Summary of Background Data. The NDI is a reliable instrument for evaluating self-rated disability due to neck pain, but there is no published Marathi version and also it has not been tested on a rural population yet. Successful linguistic and cultural translation may allow appropriate cross-cultural comparison for clinical and laboratory research analysis, even in the rural parts of the Maharashtra state of India, where English is not the language of communication. Methods. Eighty-one patients having neck pain for at least 3 months were included in the study. The NDI and visual analogue scale for pain were completed by all subjects. Test-retest reliability was determined by using intraclass correlation coefficient and Pearson correlation analysis. For the determination of construct validity, the relation between the NDI and visual analogue scale was examined by Pearson correlation analysis. Results. Intraclass correlation coefficient score for test-retest reliability was 0.95 and the Cronbach α was 0.97. For construct-related validity the correlation of the NDI–Marathi version was found to be 0.95 (P < 0.0001). These results showed that the construct validity of the Marathi version of the NDI was excellent. Conclusion. The results suggest that the Marathi version of the NDI that is validated in this study is an easy to comprehend, reliable, and valid instrument for the measurement for the limitation of activities of daily living and pain caused by neck disorders in the Marathi-speaking population. Level of Evidence: 2